Inovasi Digital dalam Pertanian Membandingkan Potensi Teknologi Open Source dan Komersial untuk Transformasi Industri - Rindi Maylinda Fitri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Digital innovation in the agricultural sector is increasingly becoming an important concern as a solution to increase agricultural efficiency and productivity. This research discusses the comparison between open source technology and commercial technology in the agricultural sector, with the aim of understanding the advantages and challenges of each in the agricultural context in Indonesia. Using a comparative descriptive approach, this research involved 30 farmers who were divided into two groups, namely farmers using open source technology and farmers using commercial technology. Data was collected through interviews, questionnaires and field observations, then analyzed descriptively to describe the use of both types of technology.The research results show that open source technology is more affordable and flexible, but is limited by a lack of technical support and integration with existing agricultural systems. Meanwhile, commercial technology offers more complete technical support and more integrated systems, but high costs are a major obstacle for small farmers. In conclusion, choosing the right technology must take into account local conditions, economic capabilities and existing technical support. This research suggests the importance of policies that support the provision of affordable technology and training accessibility for farmers to maximize the potential of digital transformation in the agricultural sector.